การแก้ไขปัญหาระบบเศรษฐกิจแบบทุนนิยมด้วยหลักบุญกิริยาวัตถุและกามโภคี/Solving the Problems of Capitalism with the Principles of Meritorious Action and Kam Phokhi - ชยาภิวัฒน์, พระครูโสภณ; ฐิตปญฺโญ, พระมหามิตร (Journal of Humanities and Social Sciences (HUSOKKU), 2019)
The objectives of the study were to provide solutions to the capitalist economic system according to the principles of Theravada Buddhism. It was analyzed using the primary sources and secondary sources. This study presented the issuing of the capitalist economic system as followed: 1) the capitalist system unequally distribute capital goods which abnormal of the human actually doing 2) the capitalist system racked over proletarians and, 3) the capitalist system racked over the humanity of Labor. Therefore, author brings solutions as the principles of Buddhism which were the principle of meritorious action deal with equal charity and the principle of enjoying of senses to solve the rack problem also in human dignity. In addition, the study proved that the principle of Buddhism significance related to social living management base on the economic system as well.